2005
DOI: 10.1021/jp047511i
|View full text |Cite
|
Sign up to set email alerts
|

TDDFT Study of One- and Two-Photon Absorption Properties:  Donor−π−Acceptor Chromophores

Abstract: We report a comprehensive time-dependent density functional theory (TDDFT) study of one-photon and two-photon absorption (OPA and TPA, respectively) spectra for donor-pi-acceptor molecules. The calculated excitation energies were generally shown to be in good agreement with experiment, particularly when compared to results from measurements carried out in a nonpolar solvent, although the oscillator strengths were overestimated in some cases. Calculated TPA cross sections applying the two-state approximation we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
113
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(126 citation statements)
references
References 95 publications
12
113
1
Order By: Relevance
“…More recently, Frediani et al 13 calculated a value of 765 GM for the higher energy transition of DIAMINO in vacuo. In spite of the energy difference ͑about 0.4 eV͒, we believe that the S 0 → S 3 transition determined in this work accesses the same 3 1 Ag state reported by Frediani et al 13 For DO3, a value of 84 GM was reported by Day et al 11 through a TDDFT/B3LYP study applying the two-state approximation and a Lorentzian line-shape for the S 0 → S 2 transition. Frediani et al 13 also studied this compound using the B3LYP functional and reported values of 327 and 247 GM for S 0 → S 2 and S 0 → S 4 transitions in vacuo, respectively.…”
Section: -7supporting
confidence: 85%
See 4 more Smart Citations
“…More recently, Frediani et al 13 calculated a value of 765 GM for the higher energy transition of DIAMINO in vacuo. In spite of the energy difference ͑about 0.4 eV͒, we believe that the S 0 → S 3 transition determined in this work accesses the same 3 1 Ag state reported by Frediani et al 13 For DO3, a value of 84 GM was reported by Day et al 11 through a TDDFT/B3LYP study applying the two-state approximation and a Lorentzian line-shape for the S 0 → S 2 transition. Frediani et al 13 also studied this compound using the B3LYP functional and reported values of 327 and 247 GM for S 0 → S 2 and S 0 → S 4 transitions in vacuo, respectively.…”
Section: -7supporting
confidence: 85%
“…The calculated oscillator strength is related to the experimental integrated intensity by the relation 11 f gf = 4.32 ϫ 10 −9…”
Section: B 1pamentioning
confidence: 99%
See 3 more Smart Citations